Study on the Vacuum Pressure and Drying Time of Freeze-drying Method to Maintain the Quality of Strawberry (Fragaria virginiana) - Rokhani Hasbullah; Nuzul Syah Putra (The University of Lampung, 2022)
This study aims to examine freeze drying techniques and the effect of freeze drying techniques on the quality of freeze-dried strawberries. The material used are strawberries obtained from farmers in Lembang, West Bandung Regency, Bandung. The fruit having postharvest age of 14-15 days after the beginning of fruit formation. Freeze drying was carried out using Buchi type Lyovapor L-200 freeze dryer. The research stage consists of sample preparation, freezing, freeze drying, and quality observation. Freezing was carried out for 110 to 120 minutes until the temperature of the fruit reaches temperature of -12°C to -15 °C. Freeze drying was carried out at temperature of -46 oC for 12 hours, 24 hours, and 36 hours. The experimental design used in this experiment was a complete randomized factorial design. The first factor was vacuum pressure (0.5 mBar and 0.1 mBar) and the second factor was drying time (12 hours, 24 hours and 36 hours). The experiment was conducted with 2 repetitions. Observed quality parameters include drying rate, moisture content, weight loss, hardness, total dissolved solids, rehydration ratio and favorability/hedonic value. The results showed that the vacuum pressure, drying time and their interaction had a significantly effect on the rate of drying, moisture content, weight loss, hardness, total dissolved solids, rehydration ratio, color and texture of the fruit, but had no significantly effect on taste and aroma. Freezing drying at a vacuum pressure of 0.1 mBar and 36 hours drying time produces the best quality of freeze-dried strawberries with hedonic score of 5 (likes) based on the panelists’ assessment. Keywords: drying, freeze drying, post-harvest, rehydration, strawberry